What are the politics of love?. Issue 4 (2nd October 2018) - Mitchell,
Abstract : ABSTRACT Beginning with the examples of Jeremy Corbyn's and Bishop Michael Curry's appeal to love, the article exposes love as an alternative power to sovereignty. Taking three seminal insights from African American Professor Bell Hooks on the importance of love's definition, love as a force and the rootedness of love in childhood experience, the article examines the etymology of the word love and the political implications of recent sociological research. Then taking note of alternative voices, contemporary advocates of the politics of love are considered and focus brought to the critical issue of breaking free from the normative default to sovereign power. Resources for societal restoration and well-being are presented with particular reference to the Christian myths of incarnation and trinity and their practical application in the postsecular world. Finally tools for healing and restoration at both the individual and corporate level are considered, and their impact within contemporary initiatives.